Increasing The Bearing Capacity of Foundations on Sandy Soil with High Water Levels Using Mini-pile - Moh. Ilham Farihi; Agata Iwan Candra; Dwifi Aprillia Karisma; Nur Addin Fatkunada; Malik Ibrahim; Bagas Naga Pratala Haryadi; Rahadi Reswara (Rekayasa Sipil, 2024)
In the Kediri Regency area, it is planned to build a 3-story shophouse as one of the supporting facilities and the community’s economic needs. This area has sandy soil conditions and a high-water table. The purpose of this study was to calculate the carrying capacity of the soil in constructing a 3-story shophouse using the Terzaghi, Mayerhof, and Hansen methods. The condition of the soil with a relatively high groundwater table made the implementation of the footplate foundation less effective, so a modification of the foundation was made, which added three mini-piles measuring 0.4x0.4x1.5m, with a design load supported by the foundation of 100 t/m². Calculations with the Mayerhof and Hansen methods have nearly identical results but have not fulfilled the planned load. At a foundation depth of up to 3 m with an SF value of 3, for the Terzaghi method: 107.75 t/m2, the Mayerhof method: 92.51 t/m2, and the Hansen method: 94.68 t/m2. The results can be used as an alternative in constructing a 3-story shophouse with sandy soil conditions and high groundwater levels. This research can also be a reference for other regions facing similar problems.